NUTRITION LITERATURE OF BANGLADESH: A BIBLIOMETRIC STUDY - S. M., Zabed Ahmed; Rahman, Md. Anisur (Malaysian Journal of Library and Information Science, 2017)
This paper presents the results of a bibliometric analysis of nutrition literature of Bangladesh. A list of periodical articles on various aspects of nutrition research of Bangladesh published during 1972 - 2006 was compiled for analysis. A total of 636 articles by 998 authors were identified. The articles were published in 100 local and foreign journals. The five-yearly distribution of nutrition literature shows that there is a rapid growth of nutrition literature from 1987 onwards. Lotka’s law is found to be applicable to nutrition literature of Bangladesh. Bradford-Zipf distribution also appears to be applicable to the literature.